2021
DOI: 10.1002/csc2.20598
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate statistical methods for analysis of safflower genetic diversity using agglomerative hierarchical cluster analysis through combination of phenotypic traits and molecular markers

Abstract: Combining phenotypic and genotypic germplasm characterization is a key to efficient and successful safflower (Carthamus tinctorius L.) breeding program by identifying valuable and confirmed parents. This study aimed to investigate and use appropriate statistical methods for such a characterization, and to identify potential genetic pools in safflower germplasm that may be useful for breeding program implementation. The genetic diversity of 45 accessions from different countries, provided by the USDA-ARS, was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
(106 reference statements)
1
1
0
Order By: Relevance
“…UPGMA method was demonstrated to generate the highest coefficient values for the majority of matrices between morphological, colorimetric, and molecular data, implying that these matrices and distances are well represented as dendrograms. In line with the current study’s findings compared to other methods, the UPGMA clustering approach was shown to provide significant correlation coefficients for genetic diversity investigations in safflower ( Houmanat et al., 2021 ), yam ( Granato et al., 2018 ), sweet potato ( Paliwal et al., 2022 ), and gladiolus ( Singh et al., 2018 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…UPGMA method was demonstrated to generate the highest coefficient values for the majority of matrices between morphological, colorimetric, and molecular data, implying that these matrices and distances are well represented as dendrograms. In line with the current study’s findings compared to other methods, the UPGMA clustering approach was shown to provide significant correlation coefficients for genetic diversity investigations in safflower ( Houmanat et al., 2021 ), yam ( Granato et al., 2018 ), sweet potato ( Paliwal et al., 2022 ), and gladiolus ( Singh et al., 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…Although molecular markers have been extensively used to evaluate species variety, extremely low or insignificant correlations have been observed among dissimilarity matrices generated using both phenotypic and molecular data ( Gupta et al., 2018 ). As a result, if the non-overlapping data is derived from phenotypic and genotypic divergence matrix, combining them may offer a full picture of a population’s variety ( Houmanat et al., 2021 ). Multivariate analysis approaches (HCA or PCA), are commonly used to precisely classify various plants based on their agro-morphological, molecular, chemical composition, or bioactivities that are regularly compared with correlation coefficients ( Granato et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%